The logistics and supply chain toolkit - Richards, Gwynne; Grinsted, Susan (Kogan Page, 2016)
"Providing practical and applicable solutions to some of the most frequently encountered problems in the industry, this updated second edition of The Logistics and Supply Chain Toolkit offers revised toolsthat reflect the latest innovations in technologies and processes. The book also includes new tools on calculating stock-holding cost, calculating ordering cost, managing slow-moving inventories, and new, additional website resources, such as worked examples. Chapters covering managing warehouses, transportation, inventory, supply chain, performance, finances, and outsourcing thoroughly explain each tool and suggest areas where they can be applied"--